Gendered participation in informal milk markets in Kenya: Implications for low emissions dairy development - Tavenner, Katie; Saxena, Tarangini; Crane, Todd A. (2018)
Gendered preferences for engagement in informal versus formal milk markets reflect differential ability to benefit from them. In Kenya, married women are likely to lose control over dairy income and decision-making when milk is marketed to formal channels, thus they often opt to sell milk through informal arrangements. Women selling to or working in the informal sector as vendors (“milk hawkers”) are circumventing male-dominated formal structures and increasing their access to income. Low emissions dairy development (LEDD) has been pursued only through the formal milk marketing sector, creating a reifying dilemma for existing power structures in terms of gendered access to dairy income. Both formal and informal market participation provide important avenues towards agency and prosperity for women and their families. Understanding the social trade-offs in market participation for both is necessary to inform to inform gender inclusive low emissions dairy development strategies.